A new species of Terelabrus (Perciformes: Labridae) from the Philippines with a key to species of Terelabrus and new record of Terelabrus dewapyle - Fukui, Yoshino (Zootaxa, 2018)
A new labrid fish, Terelabrus zonalis sp. nov., the fourth species of the genus, is described on the basis of two specimens collected from the Philippines. The new species is characterized by 44 longitudinal series scale rows, 42 pored lateral-line scales, 11–12 gill rakers (including rudiments), the main supratemporal sensory canal with 8 branches posteriorly, the area bounded by the main supratemporal and postotic sensory canals (dorsal view) with 3 scale rows, the least distance between the orbit anteroventral margin and interopercle 7.0% of standard length and 18 faint silver vertical bands on the body in preserved specimens. An underwater photograph of T. dewapyle is reported as the first record of the species from the Philippines. A key to species of Terelabrus is provided.